NON-AMERICAN BLACK WOMEN’S EMPOWERMENT: A FOURTH-WAVE FEMINISM STUDY ON CHIMAMANDA NGOZI ADICHIE’S AMERICANAH - Maria Ardianti Kurnia Sari; Nur Saktiningrum (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Racial issues have been a big problem in the United States of America since the slavery era. Although racism still exists in its society, many people are still migrating to America. For example, non-American Black women go there to try their luck to get a better education, a better job, and a better standard of living. However, some of them experience racism and gender inequality at work, as well as everywhere else in American society. Nevertheless, these experiences of racism and inequality may well be what motivates them to gain empowerment and gender equality. The qualitative method is used in this research. The primary source is a novel by Chimamanda Ngozi Adichie titled Americanah (2013). The secondary sources to support this analysis are books, journals, articles, videos, and current news related to the issues. Post-nationalist studies by John Rowe, transnationalism studies by Steven Vertovec, fourth-wave feminism ideas from Nikola Rivers and Prudence Chamberlain, and Black women’s empowerment studies by Sheila Radford-Hill and Patricia Hill Collins are used to analyze the data. The results of this research are: first, there are measures taken by non-American Black women to gain empowerment in the US, which begin with their aspirations to obtain acceptance in society. Second, the redefinition of gender equality through education, employment, and social changes leads to the acceptance of non-American Black women in society. The acceptance and empowerment become evidence of gender equality in education, employment, and social life. Isu rasisme menjadi salah satu masalah besar di Amerika Serikat sejak masa perbudakan. Meskipun rasisme masih terjadi, tetapi tidak sedikit imigran yang datang dan menetap. Wanita kulit hitam dari luar Amerika datang untuk mendapat pendidikan, pekerjaan, dan hidup layak. Tetapi, tidak sedikit mendapatkan rasisme dan ketidaksetaraan gender di dalam dan masyarakat. Dengan demikian, rasisme dan ketidaksetaraan memotivasi wanita kulit hitam non-Amerika untuk memperoleh pemberdayaan dan kesetaraan gender. Metode kualitatif digunakan dalam penelitian ini. Sumber pertama, novel karya Chimamanda Ngozi Adichie berjudul Americanah (2013). Sumber kedua untuk mendukung analisis diambil dari beberapa buku, jurnal, artikel, video, dan berita yang berhubungan dengan isu yang dibahas. Beberapa teori yang digunakan untuk menganalisis, yakni teori pos-nasionalis dari John Rowe, transnasionalisme dari Steven Vertovec, feminisme gelombang keempat dari Nikola Rivers dan Prudence Chamberlain, dan pemberdayaan perempuan berkulit hitam dari Sheila Radford-Hill dan Patricia Hill Collins. Berdasarkan hasil analisa, pertama, pemberdayaan wanita kulit hitam non-Amerika dimulai dari perjuangan mereka untuk mendapatkan pemberdayaan dari masyarakat. Proses perjuangan dan keberanian yang menuntun mereka untuk bisa beradaptasi dengan situasi di Amerika. Kedua, mendefinisikan kesetaraan gender dalam dunia pendidikan, pekerjaan, dan perubahan sosial. Beberapa dampak pemberdayaan menjadi bukti pencapaian kesetaraan gender dalam dunia pendidikan, pekerjaan, dan perubahan kehidupan sosial.